2017
DOI: 10.1159/000456706
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on Early Patterns of Respiratory Disease among Extremely Low Gestational Age Newborns

Abstract: Background: The analysis of early patterns of lung disease among preterm infants may help to identify predictors of pulmonary deterioration. Objectives: To analyze FIO2 requirement in the first 14 days of life among preterm infants and to find predictors of bronchopulmonary dysplasia (BPD). Methods: Retrospective cohort study. Setting: 3 Italian level III NICUs. Population: infants born between 240/7 and 276/7 weeks' gestational age (GA) who survived to 14 days. A consecutive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…To date, no published studies have investigated long‐term pulmonary outcome in preterm infants with different ERP. We found that the degree of prematurity, which is strongly associated with ERP as we previously showed, was significantly associated with 36w‐SFR only among infants without BPD. Among infants with BPD, there was a non‐significant direct correlation between GA at birth and 36w‐SFR.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…To date, no published studies have investigated long‐term pulmonary outcome in preterm infants with different ERP. We found that the degree of prematurity, which is strongly associated with ERP as we previously showed, was significantly associated with 36w‐SFR only among infants without BPD. Among infants with BPD, there was a non‐significant direct correlation between GA at birth and 36w‐SFR.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, perinatal risk factors related to growth restriction and inflammation may increase the risk of BPD in preterm infants . We previously showed that human milk feeding was associated with less severe ERP, as it may contain trophic factors that might protect the lungs from injuries and improve lung and vascular growth . Given the results of this study, we speculate that the beneficial effects of human milk are sustained and result in a more efficient oxygen diffusion at 36 weeks’ PMA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors noted that the SFR values at 36 weeks (36w‐SFR) was significantly different between BPD (using the “physiologic” definition) and non‐BPD infants [371 [316‐419] vs 467 [460‐471]; P < 0.001]. In addition, the 36w‐SFR also was significantly different according to the early respiratory disease patterns (ERP), as described in an earlier publication by the same group of investigators . Significant differences were found both in BPD and in non‐BPD patients according to ERP in the study by Nobile et al (Figure 2; P < 0.001; the Kruskal Wallis test).…”
mentioning
confidence: 99%